THIKCNESS DESIGN OF RIGID PAVEMENT ON THE ROAD SECTION GUBERNUR SUBARJO (STA 6 + 000 S / D STA 11 + 000) BANJARMASIN - Ibnu Kasfuddin; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2018)
Gubernur Subarjo Jalan Banjarmasin is one of inter-provincial road traffic of that activity is quitehigh. As the road plays an important role road transport is still experiencing problems namely: increasing the amount of traffic, especially on heavy vehicles which resulted in pavement damagethese. Therefore it is necessary to choose the alternative pavement suitable for use at this location according to road conditions and environment. This thesis aims to calculate the pavement thickness and the draft budget the Gubernur Subarjo roads Banjarmasin.On the roads studied, pavement used is rigid pavement structure (Rigid Pavement) the calculation using the method Pavement Design Manual No. 02 / M / BM / 2013 which is controlled by the method of Pd T-14-2003 and for the calculation of the budget using the guidelines Employment Analysis Unit Price (AHSP), 2013. Total segment length is used as a research location is 5000 m long.The results obtained for road width of 7.5 m and 2 m wide shoulders, a new pavement covering the rigid pavement with 265 mm thick, with thick layers of foundation LMC and Aggregate Class A is 150 mm. Budget obtained Rp. 29.903 billion corresponding unit price is determined.